Comparative transcriptomic signatures of virulent and attenuated Mycobacterium bovis growing in vitro and in mice - Abdelaal, Hazem F. M.; Salem, Lama M.; Steinberg, Howard; Talaat, Adel M. (Frontiers in Cellular and Infection Microbiology, 2025)
Bovine tuberculosis (bTB), caused by Mycobacterium bovis (M. bovis), poses a significant global health and economic burden. Despite extensive research, a comprehensive understanding of M. bovis pathogenesis, particularly its transcriptional adaptation across different growth phases and within the host environment, remains incomplete. Here, we performed a comprehensive transcriptomic analysis of virulent M. bovis and the attenuated M. bovis BCG strain (BCG) across early-log, mid-log, and stationary growth phases to elucidate the molecular underpinnings of their phenotypic distinctions. Differential expression was computed with DESeq2, and coexpression modules were derived with WGCNA. Gene sets emphasized secretion systems and lipid metabolism. For biological context, selected transcripts were quantified by qRT PCR from lungs of infected C3HeB FeJ mice at four and sixteen weeks. Both strains remodeled transcription across growth, highlighting significant differences in pathways related to cell wall biosynthesis, lipid metabolism, transcriptional regulation, protein secretion, and the PE/PPE protein family. Notably, the Virulent M. bovis showed higher expression of envelope lipid genes, including the Pks13 and FadD32 locus, and a subset of DosR targets, while BCG emphasized stress and metabolic adjustment. Coexpression analysis provided a systems-level view of the transcriptional programs governing M. bovis and M. bovis BCG physiology, identifying key modules of co-expressed genes that regulate small molecules transport, amino acid biosynthesis and immune evasion in M. bovis. Furthermore, we analyzed M. bovis transcriptional responses during murine lung infection, identifying a core set of DEGs linked to host-pathogen interactions and mechanisms of persistence. These findings offer novel insights into M. bovis adaptation strategies and transcriptomic signatures that separate virulent M. bovis from attenuated BCG across growth and in the host. Differences in secretion capacity and lipid metabolism align with known deletions and attenuation mechanisms, and the in vivo measurements provide context for prioritizing pathways and BCG substrain evaluation.